2006
DOI: 10.1073/pnas.0609463104
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a biomarker for sleep drive in flies and humans

Abstract: It is a common experience to sacrifice sleep to meet the demands of our 24-h society. Current estimates reveal that as a society, we sleep on average 2 h less than we did 40 years ago. This level of sleep restriction results in negative health outcomes and is sufficient to produce cognitive deficits and reduced attention and is associated with increased risk for traffic and occupational accidents. Unfortunately, there is no simple quantifiable marker that can detect an individual who is excessively sleepy befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
101
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(105 citation statements)
references
References 39 publications
1
101
3
Order By: Relevance
“…A similar disassociation between wake time and sleep homeostasis can be achieved by comparing flies treated with caffeine or methamphetamine. 1,7 Both caffeine and methamphetamine each produce sustained periods of waking and similar locomoter activity profiles. However, unlike caffeine, flies do not compensate for the lost sleep accrued during methamphetamine-induced waking.…”
Section: S U P P L E M E N Tmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar disassociation between wake time and sleep homeostasis can be achieved by comparing flies treated with caffeine or methamphetamine. 1,7 Both caffeine and methamphetamine each produce sustained periods of waking and similar locomoter activity profiles. However, unlike caffeine, flies do not compensate for the lost sleep accrued during methamphetamine-induced waking.…”
Section: S U P P L E M E N Tmentioning
confidence: 99%
“…With that in mind, a goal of our laboratories has been to develop a rational strategy to expedite the identification of candidate biomarkers. 1 We began with the assumption that since both the genetic and environmental context of a gene can influence its behavior, an effective test of sleep loss will likely be composed of a panel of multiple biomarkers. That is, we believe that it is premature to exclude a candidate analyte simply because it might also be modulated in response to other conditions (e.g., illness, metabolism, sympathetic tone, etc.).…”
mentioning
confidence: 99%
“…In an extension of this undertaking, salivary RNA was also applied successfully to array analysis by an independent group to identify new saliva identifying mRNAs [19]. Lastly, salivary amylase mRNA (and protein) were shown to be highly correlated with sleep deprivation [20].…”
Section: Salivary Transcriptomementioning
confidence: 99%
“…A gene expression study identified salivary amylase as a biomarker of sleep drive in both fruit flies (Drosophila melanogaster) and humans. 49 Indeed, heterozygote individuals with a single copy of the c.22G > A (rs73598374) polymorphism for adenosine deaminase differ significantly from homozygote individuals with respect to vulnerability to sleep loss, exhibiting both a reduction in sustained attention and an elevation in salivary α-amylase activity during periods of prolonged waking. 55 Although many of these measures of sleepiness appear promising, the lack of specificity among many, if not all, of the sleep reporter and regulatory substances identified to date has led some to suggest that proper measurement of sleepiness will ultimately require simultaneous monitoring of numerous analytes.…”
Section: Other Measures Of Sleepinessmentioning
confidence: 99%
“…Methods of quantifying sleepiness have been proposed based on changes in behavioral factors such as response time 6,46 and other measures of attention, as well as various electrophysiological factors such as changes in the power for a particular type of electroencephalographic wave. 47 Other methods for measuring sleepiness have focused on changes in the composition of serum, 48 saliva, 49 cerebrospinal fluid, 50,51 exhaled breath, and exhaled breath condensate. 52 Inflammatory factors such as IL-6, TNF-α, von Willebrand factor, and C-reactive protein 53,54 have drawn considerable attention.…”
Section: Other Measures Of Sleepinessmentioning
confidence: 99%